Internalization Of Moderate Religious Values In Islamic Religious Education Materials For Students At Sibolga State Senior High School 3 - Sihotang, Jahrul; Budianti, Yusnaili; Sumanti, Solihah Titin (Journal of Educational Sciences, 2025)
This study aims to describe and analyze the internalization process of religious moderation values within the Islamic Religious Education (PAI) curriculum for students at SMA Negeri 3 Sibolga. Religious moderation emphasizes tolerant, just, and balanced (tawazun) attitudes, while rejecting all forms of violence and extremism. The internalization of these values in religious education is essential as part of character building for students to become not only religious individuals but also capable of living harmoniously in a multicultural society. This research employs a qualitative approach with a descriptive method. Data collection techniques include in-depth interviews, direct observation, and documentation study. The research subjects consist of Islamic Religious Education teachers, students, and the school principal. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the internalization of religious moderation values at SMA Negeri 3 Sibolga is carried out through several strategies: (1) integrating moderation values into the Islamic Education curriculum content, (2) developing contextual and dialogical teaching methods, (3) conducting inclusive and collaborative religious activities, and (4) modeling by teachers in daily behavior. However, the implementation faces several obstacles, such as the negative influence of social media, students’ limited understanding of moderation, and the lack of comprehensive teacher training on religious moderation